Development of whey-fruit-based energy drink premixes - Patil, Shital; Sahoo, A K; Patil, N J; Lokhande, S M; Ranveer, R C (Journal of Postharvest Technology, 2019)
Moment vitality powder by utilizing Spray drying strategy is later, straightforward, monetary and beneficial technique. The readied watermelon juice and  protenious whey with caffeine added substances gives moment incitement which gives better quality item. The emulsion for splash drying was set up  by 60:40 watermelon and concentrated whey with 10% sugar, 75 mg of caffeine and 0.50 mg of CMC which was advanced based on Sensory  Analysis. The readied emulsion was blended with various convergence of Malto-dextrin powder as emulsifying operator which impact on the  profitability of the last premix. 5% maltodextrin powder gives most extreme yield when contrasted with 3% maltodextrin. 75 mg of caffeine gives  impeccable incitement and concentrated whey give greatest protein substance to premix. The last premix was pressed into metalized film which  increment the sensorial and microbial security of the item. Dampness content and disintegration time increments though water movement and mass  thickness diminishes amid the multi month of capacity. At long last outcome gives the better quality, low water action, less demanding transport and  capacity premix was readied.
Keywords: Premix; Spray Drying; Watermelon; Whey protein